2022
DOI: 10.1021/acs.biochem.2c00610
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Mechanisms of Aromatic and Aryl-Methyl Substituent Hydroxylation by the Rieske Monooxygenase Salicylate 5-Hydroxylase

Abstract: The hydroxylase component (S5HH) of salicylate-5-hydroxylase catalyzes C5 ring hydroxylation of salicylate but switches to methyl hydroxylation when a C5 methyl substituent is present. The use of 18 O 2 reveals that both aromatic and aryl-methyl hydroxylations result from monooxygenase chemistry. The functional unit of S5HH comprises a nonheme Fe(II) site located 12 Å across a subunit boundary from a one-electron reduced Riesketype iron−sulfur cluster. Past studies determined that substrates bind near the Fe(I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 154 publications
0
3
0
Order By: Relevance
“…Recent studies have indicated that an Fe(III)-superoxo species is likely the key oxidant that is used to facilitate the monooxygenation and dioxygenation reactions performed by salicylate 5-hydroxylase and benzoate 1,2-dioxygenase, respectively (Supplementary Fig. 1 ) 32 – 34 . However, to date, despite several investigations that indicate formation of the reactive Fe-based intermediate for catalysis is the rate limiting step of a Rieske oxygenase catalyzed reaction, the nature of the oxidizing species for most members of this enzyme class remains to be defined 35 37 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that an Fe(III)-superoxo species is likely the key oxidant that is used to facilitate the monooxygenation and dioxygenation reactions performed by salicylate 5-hydroxylase and benzoate 1,2-dioxygenase, respectively (Supplementary Fig. 1 ) 32 – 34 . However, to date, despite several investigations that indicate formation of the reactive Fe-based intermediate for catalysis is the rate limiting step of a Rieske oxygenase catalyzed reaction, the nature of the oxidizing species for most members of this enzyme class remains to be defined 35 37 .…”
Section: Introductionmentioning
confidence: 99%
“…Another recent example reported by Rogers et al shows that the Rieske monooxygenase salicylate 5-hydroxylase (S5HH) catalyzes C5 ring hydroxylation of salicylate, but switches to methyl hydroxylation when a C5 methyl substituent is present. [172] Interestingly, it was shown that S5HH exhibits high sensitivity to the electronic structure of the substrate in the rate constant of electron transfer from the Rieske cluster to the mononuclear Fe site. When S5HH switches from aromatic to methyl hydroxylation, the Rieske cluster oxidation kinetics and product formation exhibit opposite deuterium isotope effects during the hydroxylation of the methyl substituent, giving new insight into the mechanisms of Rieske monooxygenation.…”
Section: Chembiochemmentioning
confidence: 99%
“…Another recent example reported by Rogers et al. shows that the Rieske monooxygenase salicylate 5‐hydroxylase (S5HH) catalyzes C5 ring hydroxylation of salicylate, but switches to methyl hydroxylation when a C5 methyl substituent is present [172] . Interestingly, it was shown that S5HH exhibits high sensitivity to the electronic structure of the substrate in the rate constant of electron transfer from the Rieske cluster to the mononuclear Fe site.…”
Section: Reactivities Of Rosmentioning
confidence: 99%